Dissimilaridade genética e dialelos em cenoura por meio da análise de caracteres agronômicos e fenotipagem por imagem - Coelho, Fernanda Gabriela Teixeira (2024)
Carrot (Daucus carota L.) is a vegetable from the Apiaceae family and stands out for its great global economic importance in terms of production area, market value, pleasant flavor, and nutritional composition. However, studies on carrots, especially in tropical climates, are still limited. Therefore, the objective was to identify heterotic groups and tropical carrot parents with great combining ability in the exploration of hybrids through agronomic evaluations and image phenotyping. The experiments were carried out in the city of Carandaí, MG. Fifty-seven tropical carrot entries from Seminis (Brazil) and three commercial varieties were evaluated. An agronomic evaluation was carried out, and two flights were conducted with a Remotely Piloted Aircraft (RPA), before and after harvest. Then, 5 carrot entries were selected in their fertile and male-sterile versions, which were crossed in a balanced diallel model (5 x 4). The hybrids, parents and three commercial entries as controls were evaluated in the summers of 2020/2021 and 2021/2022. The existence of genetic variability was observed among the tropical carrot entries and the formation of six groups through an artificial neural network using the Kohonen self-organizing map. The vegetation indices calculated from the RGB image (BI, HI, HUE, NGRDI, SCI and VARI), as well as the calculated commercial, discard, and total root areas, had significant correlations with agronomic traits. Ten top entries were selected by genotype-ideotype distance. Through diallel analysis, it was verified that several agronomic traits in tropical carrots present additive genetic effects. There was emphasis on the CGC of parents 5, 4, and 2 and the CEC of hybrids 1x2, 3x5, 1x5 and 5x3. The 2x4, 3x1, 4x1, and 4x2 hybrids demonstrated higher metabolite contents in the leaf and root. And the 3x5 and 5x3 hybrids, which stood out for CEC, showed high levels of total carotenoids and lycopenes in the root. With these data, it appears that tropical carrot materials can be evaluated indirectly via remote sensing, and there is the possibility of obtaining superior hybrids for the tropical carrot market.